Etične dileme v rehabilitaciji otrok - Logar, Svetlana (Rehabilitacija (Ljubljana), 2017)
Considering the guiding ethical principles, such as autonomy, credibility (facilitating informed consent), beneficence and harmlessness, justice (equality), privacy and confidentiality, integration into the therapeutic process, as well as the specificities of rehabilitation of children, such as epidemiology, course of rehabilitation and close cooperation with the child, family and environment, the paper presents some areas of ethical dilemmas in the field of rehabilitation of children. In resolving ethical dilemmas, it is very important to consider developmental characteristics of the child, the active involvement of the child or adolescent in decision-making processes within rehabilitation programs, active involvement of the family, the principles of family-centred care of children and families, the implementation thereof, implementation of social and economic rights, participation in educational programs and the wider social environment. It is also important to be aware of the ethical dilemmas in rehabilitation research.
Keywords: adolescent; Child; družina; educational institutions; ethical issues; ethics; etične dileme; family; mladostnik; otrok; rehabilitacija; Rehabilitation; terapevtski program; therapeutic program; vocational rehabilitation; vzgojnoizobraževalne ustanove